Direct Simulation of Charge Transport in Graphene Nanoribbons (Communications in Computational Physics, 2022)
Graphene nanoribbons are considered as one of the most promising ways todesign electron devices where the active area is made of graphene. In fact, graphenenanoribbons present a gap between the valence and the conduction bands as in standard semiconductors such as Si or GaAs, at variance with large area graphene which isgapless, a feature that hampers a good performance of graphene field effect transistors.To use graphene nanoribbons as a semiconductor, an accurate analysis of theirelectron properties is needed. Here, electron transport in graphene nanoribbons isinvestigated by solving the semiclassical Boltzmann equation with a discontinuousGalerkin method. All the electron-phonon scattering mechanisms are included. Theadopted energy band structure is that devised in [1] while according to [2] the edgeeffects are described as an additional scattering stemming from the Berry-Mondragonmodel which is valid in presence of edge disorder. With this approach a spacial 1Dtransport problem has been solved, even if it remains two dimensional in the wave-vector space. A degradation of charge velocities, and consequently of the mobilities, isfound by reducing the nanoribbon width due mainly to the edge scattering.
Keywords: Graphene nanoribbons; bipolar charge transport; discontinuous Galerkin method.